Influence of Audit Technology Implementation on Efficiency and Accuracy of Audits in Public Companies: A Case Study of Manufacturing Companies in Indonesia - Nasution, Raden; Dailibas, Dailibas; Chaerudin, Chaerudin; Harahap, Muhammad Nasim; Mutaufiq, Ali; Kumala, Destiana (International Journal of Artificial Intelligence Research, 2024)
This research discusses the influence of the application of audit technology on audit efficiency and accuracy in manufacturing companies in Indonesia. This research uses a type of quantitative research with a survey approach with the method used is saturated sampling/census, with a sample of 26 manufacturing companies in Indonesia. This research data analysis technique uses PLS software version 3.0 (Partial Least Square). The results of the research showed that the application of audit technology had a positive and significant effect on efficiency with a statistical t value of 31.066 > 2.055 and a P-value of 0.000, this means that techniques for implementing audit technology such as audit information systems , big data analytics. , and AI (artificial intelligence) technology can significantly improve the efficiency of the audit process. This technology allows auditors to conduct deeper analysis of transaction data and complex patterns, identifying anomalies or potential risks more quickly and precisely. The application of audit technology has a positive and significant effect on audit accuracy with a statistical t value of 76.415 > 2.055 and a P-value of 0.000, this means that accurately, audit technology can also minimize human error in the audit process, because it can carry out automatic testing and broader analysis of available data. This increases the accuracy of the financial reports produced, which is one of the main objectives of the audit process in supporting transparency and public trust in public companies.